IBNU KHALDUN'S THOUGHTS IN PRESENT EDUCATIONAL CONTEXT - Suriadi adi Samsuri; Mowafg Maswuwd (FORUM PAEDAGOGIK, 2023)
This article aims to discuss the formulation of vision, mission and values in Islamic educational institutions according to Ibn Khaldun. This study focuses on (1) stakeholder analysis in Islamic education institutions, (2) how the vision, mission, and values are stated, (3) what are the components of the strategy, and how is the concept of social responsibility. Islamic educational institutions actually have various kinds of stakeholders. If viewed from several divisions of stakeholders in educational institutions, primary, secondary, and tertiary stakeholders will be identified. The main stakeholders of the madrasa are the students themselves, however, students who come to the madrasa due to funding from the parents of these students, so these two components are the components that educational institutions must pay the most attention to.